THE ROLE OF LEGAL POLITICS IN THE FORMATION OF LEGISLATION IN INDONESIA AS A MEANS OF REALIZING STATE GOALS - Amiruddin Lannurung; Patwari (Faculty of Law, Universitas Pekalongan, 2025)
This research discusses the role of legal politics in the formation of laws and regulations in Indonesia as an instrument to realize state goals. Legal politics has a strategic role in determining the direction and substance of regulations made by the government and legislature, so that it is able to reflect constitutional values and national interests. The research method used is a normative method with a statute approach and a conceptual approach. Data is collected through literature studies that include analysis of laws and regulations, legal doctrines, and related scientific literature. The results of the study show that legal politics is the main factor in forming regulations that are not only based on positive legal norms, but also consider social, economic, and political aspects. In addition, legal politics plays a role in directing legislation to be in line with Pancasila and the 1945 Constitution of the Republic of Indonesia as the basis of state ideology. The findings of this study confirm that the effectiveness of the formation of laws and regulations is highly dependent on the stability of legal politics that is progressive, responsive, and oriented to the interests of the people.